2015
DOI: 10.1016/j.ijheatmasstransfer.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Local Nusselt number enhancements in liquid–liquid Taylor flows

Abstract: a b s t r a c tThermal management has emerged as a critical requirement to ensure the performance and reliability of electronic devices and systems. System level heat fluxes are approaching the limits of conventional forced air cooling, and there is a need to develop alternative cooling techniques for devices such as processors, power amplifiers and laser arrays. This paper examines the potential heat transfer enhancements of a two phase liquid-liquid Taylor flow regime. The primary focus of the work was to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Many experiments have been performed to measure the heat transfer enhancement in microchannels with droplets, slugs, or plugs [9]. Some experiments used cylindrical microtubes [10,11,12,13], while others used rectangular microchannels [14,15,16,17]. Their experimental results showed significant enhancement of heat transfer when comparing with single phase flow, and the Nusselt numbers are several times higher than the single phase counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…Many experiments have been performed to measure the heat transfer enhancement in microchannels with droplets, slugs, or plugs [9]. Some experiments used cylindrical microtubes [10,11,12,13], while others used rectangular microchannels [14,15,16,17]. Their experimental results showed significant enhancement of heat transfer when comparing with single phase flow, and the Nusselt numbers are several times higher than the single phase counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…This gives confidence in enhancing heat transfer utilising two-phase liquid-liquid plug flow. It must be noted that studies by Liu et al [14] and Che et al [10] report that shorter plug lengths lead to higher heat transfer, which is in disagreement to Eain et al [11].…”
Section: Two-phase Heat Transfermentioning
confidence: 79%
“…The fundamental concepts from these studies should be applicable to the research study with the exception of using ferrofluid plugs instead of DIW. Eain et al [11] conducted experimental investigations examining potential heat transfer enhancements of a two-phase liquid-liquid Taylor flow regime. They studied the effects of slug length and carrier phase variations of Pd5, Dodecane and AR20 silicone oils on the local Nu.…”
Section: Two-phase Heat Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Though plenty of studies in single phase systems in microchannels have been reported [4], a few experimental studies for two phase liquid-liquid systems have been carried out by researchers [98][99][100]. Systems used were water-light mineral [98]; siliconoilwater [99] and Water-hexadecane [100]. All the authors have observed slug flow in their investigations.…”
Section: Experimental Studies Of Heat Transfer In Microchannels Involving Liquid-liquid Two Phase Flowmentioning
confidence: 99%